Composition and structure of Heteroptera communities (Hemiptera) in high altitude habitats of a national protected area in Argentina - Cava, María Belén (2012)
Composition and structure of Heteroptera communities (Insecta: Hemiptera) in high altitude habitats of a national protected area in Argentina. One of the basic strategies to protect biodiversity is the establishment of National Parks and other protected areas. Los Cardones National Park (Salta, Argentina) is of great importance because it attempts to preserve a representative sample of Andean biomes above 2700masl, such as Monte Occidental , the Puna-Prepuna and upper reaches of the Yungas. We describe the composition and structure of an inventory of true bugs sampled over a 1-year period in the three ecoregions represented in this protected area. Twenty-nine species of Heteroptera were recorded, including five new records for the Province of Salta. All species are first records to the park. The inventory obtained represents 85.29% of the total estimated by non-parametric estimator (Chao1), with Miridae as the best represented family. The results contribute to knowledge of the Heteroptera of the protected area and provide a basis for comparisons with other studies conducted in other high altitude habitats.